Democracy on Trial: Social Movements and Cultural Politics in Postauthoritarian Taiwan. Hong Kong: The Chinese University Press, 2013 - Ya-Chung Chuang (Сравнительная политика)
Democracy on Trial: Social Movements and Cultural Politics in Postauthoritarian Taiwan. Hong Kong: The Chinese University Press, 2013